(untitled) (Religious dialogue and cooperation, 2024)
Four major ‘ideal type’ models may be distinguished in cultural relations in society: Monocultural (monopoly of one culture), Multicultural (living apart together, in mutual tolerance), Secular (rule of law, equality, culturally neutral) and Intercultural (different cultures connected in equivalence). Cultural diversity will become more prominent in the wake of increasing globalisation and migration – which makes the challenge of connecting cultures more urgent than ever. This essay reports on a content analysis of the proceedings of two European conferences on religious dialogue and cooperation (2019, 2022) in Struga, North-Macedonia. These suggest that today cultures are being disconnected rather than connected. Where several major cultures co-exist they struggle for cultural priority; where one dominant culture exists it defends itself against intrusion by other cultures. At the same time there is a persistent pull towards the secular model. This stands in the way of coming closer to the intercultural model. Movement in the direction of an intercultural model appears to remain restricted to statements of political and religious correctness or incidental grass roots initiatives. This essay will offer a survey of policies that have had a positive and negative effect on connecting cultures, leading to explore the transition to an intercultural society. The critical variables in that process will be identified and analysed, leading to proposals for proactive policies to strengthen the connecting process.